Exposure to Crude Oil and Chemical Dispersant May Impact Marine Microbial Biofilm Composition and Steel Corrosion - Salerno, Jennifer L.; Little, Brenda; Lee, Jason; Hamdan, Leila J. (Frontiers in Marine Science, 2018)
The release of hydrocarbons and chemical dispersant in marine environments may disrupt benthic ecosystems, including artificial reefs, formed by historic steel shipwrecks, and their associated organisms. Experiments were performed to determine the impacts of crude oil, dispersed crude oil, and dispersant on the community structure and function of microorganisms in seawater (SW) and biofilms formed on carbon steel, a common ship hull construction material. Steel corrosion was also monitored to illustrate how oil spills may impact preservation of steel shipwrecks. Microcosms were filled with seawater (SW) and incubated at 4ºC. Carbon steel disks (CSDs) were placed in each tank, and tanks were amended with crude oil and/or dispersant or no treatment. SW and CSD biofilms were sampled biweekly for genetic analysis using Illumina sequencing of 16S ribosomal RNA gene amplicons. Predicted and sequenced bacterial metagenomes were analyzed to examine impacts of oil and dispersant on metabolic function. Gammaproteobacteria, Alphaproteobacteria, and Flavobacteriia dominated SW and biofilms. Bacterial community structure differed significantly between treatments for SW and biofilms. OTUs affiliated with known (Pseudomonas) and potential (Marinomonas) hydrocarbon-degraders were roughly twice as abundant in biofilms treated with oil and dispersed oil, and steel corrosion of CSDs in these treatments was higher compared to control and dispersant treatments. OTUs affiliated with the Rhodobacteraceae family (biofilm formers and potential oil degraders) were less abundant in the dispersant treatment compared to other treatments in biofilm and SW samples, but OTUs affiliated with the Pseudoalteromonas genus (biofilm formers and proposed hydrocarbon degraders) were more abundant in dispersant-treated biofilms. Overall, functional gene analyses revealed a decrease in genes (predicted using PICRUSt and observed in sequenced metagenomes) associated with hydrocarbon degradation in dispersant-treated biofilms. This study indicates that exposure to oil and dispersant could disrupt the composition and metabolic function of biofilms colonizing metal hulls, as well as corrosion processes, potentially compromising shipwrecks as ecological and historical resources.